Impact of POSPAV Service to Company Performance PT Pos Indonesia (Persero) - Widjana, Nabila Zahra; Noveria, Ana (Journal of Business and Management, 2014)
In its historical development, postal industry can be said as courier industry delivering any written message from the sender to the receiver, As time goes by the postal service provider of either government or public all over the world should be in the possession of business model capable of supporting the sustainability. PT. Pos Indonesia engaged in postal service and already does diversification in service with applying the payment of PosPay, the growth of PosPay segment products (SOPP) offered by Pos Indonesia is supported by the growing level of two industries that become the main stimulants for the product segment, subscription-based industry (credit card) and financing industry (leasing and consumer financing). For the overall financing service product owned by Pos Indonesia, the superiority lies in the well-established networks around Indonesia. The analysis used in this case is financial performance. There are several methods than can be considered to assess the financial performance of company. The methods are Financial Statement and Financial Ratio Analysis, Common Size Income Statements Analysis, DuPont Analysis and BUMN Framework. From each methods, there will be results that explain how growth financial PT. Pos Indonesia every year. Â PT Pos Indonesia (Persero) has experienced loss it is because fewer people are using the service at the post office because of the development of the Information Technology advances in the field of digital information. So the conventional information services performed by the post office down quickly. The post office remains operational costs for payroll, utilities, raw materials and transportation still running. Based on these facts, PT Pos Indonesia (Persero) adjusts the service to start embracing information technology to be one of their services. Ultimately PT Pos Indonesia (Persero) started launching financial products involving information technology called PosPay. Some of the results obtained from the analysis show that the service PosPay indeed a major impact on the performance of PT Pos Indonesia (Persero). But on the other hand there are several shortage from this product such as the need of infrastructure and human resource which create the swell of operating cost, also this product still not able to change the liquidity and debt aspect to good condition.Keyword: Postal Service, PosPay, Financial Performance, Pos Indonesia, Post Office